STUDY OF ISOTHERMS OF WATER VAPOR SORPTION FOR HYDROPHILIC POLYMERS - Michael Yacob Ioelovich (Химия растительного сырья, 2022)
Various models and equations of water vapor (WV) sorption for hydrophilic polymers were considered. However, these models often do not correspond to the sorption mechanism. This study is based on the thermodynamics in binary systems and the Van Krevelen method of polar group contributions in the sorption of WV. Moreover, it was shown that the mechanism of WV sorption by various hydrophilic polymers is the absorption of water molecules in the volume of amorphous domains of these polymers. As a result, a universal physicochemical equation was proposed allowing adequately to describe the sorption isotherms of WV by amorphous hydrophilic polymers knowing only the chemical formulas of repeating units of these polymers. To calcu-late the sorption isotherms for semicrystalline polymer samples, it is necessary to use an additional parameter, namely the degree of amorphicity (Y). The adequacy of the derived equation was verified for samples of cellulose and other natural polysaccharides, as well as for samples of synthetic hydrophilic polymers such as polyvinyl alcohol, polyamide-6, and polycaprolactone having various Y-values. The verification showed that the experimental isotherms are almost identical to the isotherms calculated by the universal equation.